Tribocorrosion behavior of nickel-free duplex and 316L stainless steels fabricated by laser powder bed fusion in artificial seawater - Anand, Abhinav; Nayak, Chinmayee; Mäkilä, Ermei; Que, Zaiqing; Piili, Heidi; Goel, Sneha; Salminen, Antti; Ganvir, Ashish (Elsevier, 2026)
In this work, nickel-free duplex stainless steel (NiFDSS) and 316L stainless steel were produced by laser powder bed fusion (PBF-LB/M) under optimized parameters, reaching 98.83 % and 99.80 % relative densities, respectively. Microstructural analysis showed transformation from fully ferritic in the as-built condition to duplex after heat treatment (950 °C/1 h, followed by water quenching) for NiFDSS. Corrosion resistance was evaluated by potentiodynamic polarization in artificial seawater (0.6 M NaCl with pH 8.2), while tribocorrosion performance was measured in a ball-on-disc setup under the same electrolyte. As-built NiFDSS exhibited a lower corrosion current density (1.30 μA/cm2) than 316L (1.78 μA/cm2), and heat treatment further reduced it to 0.65 μA/cm2, reflecting enhanced corrosion resistance. Under tribocorrosion, NiFDSS and heat-treated NiFDSS maintained lower corrosion rates but incurred higher wear rates than 316L, driven by residual porosity along with cleavage-prone fragmentation in the as-built alloy and sigma-phase-assisted cracking after heat treatment. Overall, PBF-LB/M of NiFDSS provided superior corrosion resistance while exhibiting lower wear performance than 316L. Porosity control through further PBF-LB/M parameters refinement and heat-treatment optimization is required to minimize residual pores and suppress sigma-phase precipitation, thereby improving wear resistance of NiFDSS.